Praslavjanskoe *(w)os? 'us' - Saenko, M. N. (Jezikoslovni zapiski, 2025)
This article explores whether the form *wos? or *os? existed in Late ProtoSlavic. It is demonstrated that Old Church Slavic, Old Serbian, and Old Czech data speak rather in favor of the second variant. The modern Czech form vousy ‘beard’ cannot be considered a reliable argument. At the same time, it is shown that the reconstruction *os? does not contradict the traditional etymology of this word and does not support the alternative version put forward by Oleg Trubachev. The author proposes two explanations for the loss of initial w- by the form *(w)os? in Late Proto-Slavic.
Keywords: etimologija; etymology; praslovanščina; Proto-Slavic language